Komposisi 7:3 Terhadap Histerisis Material (B7S3)HF - Musfirah Cahya Fajrah (Institut Sains dan Teknologi Nasional, 2023)
Abstract In this research has conducted on the analysis of the material BSHF, the result of mixing BHF substitution with Sr on the composition of 7: 3 of material notation (B7S3)HF. The manufacturing process is done by wet milling with alkhohol mixed for 40 hours, followed by heating temperature 1200oC for 2 hours. During the milling process with an interval of 10 hours, the powder take off to measuring the diameter of the particle with PSA. Material that have been in the form of crystals and re-milling for 4 hours and then follow by the sonication for 6 hours to get nano size of B7S3HF material. Material in this nano size at 70 kN compaction pressure to get the bulk to be analyzed by XRD, Permagraph, and SEM. From these results identified the effect on inducted for the magnetic properties of the material B7S3HF. Keywords:, Mechanical Alloying, sonication, magnetic induction ,hysteresis